2016
DOI: 10.1002/jhbp.377
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐375 and miR‐200c as predictive biomarkers of islet isolation and transplantation in total pancreatectomy with islet autotransplantation

Abstract: We concluded that miR-375 and miR-200c could potentially serve as novel biomarkers in predicting the islet yield in islet isolation and the metabolic function after transplantation for chronic pancreatitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Furthermore, we reported that miR-375 and miR-200c are solid biomarkers to anticipate pretransplantation and posttransplantation graft function in TPIAT patients. 14,15 MiR-375 is highly expressed in the islets and is found at a quantity of about 5.66 × 10 −2 fmol per human IEQ. In addition, it regulates glucose-mediated insulin secretion in the islets by targeting the exocytosis-related myotrophin protein producing gene MTPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we reported that miR-375 and miR-200c are solid biomarkers to anticipate pretransplantation and posttransplantation graft function in TPIAT patients. 14,15 MiR-375 is highly expressed in the islets and is found at a quantity of about 5.66 × 10 −2 fmol per human IEQ. In addition, it regulates glucose-mediated insulin secretion in the islets by targeting the exocytosis-related myotrophin protein producing gene MTPN.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, recently, we reported that miR-375 and miR-200c are biomarkers that predict posttransplantation graft function in patients with TPIAT. 15 In the current study, we measured the absolute amount of miR-375, miR-200c, and C-peptide released during multiple stages of the islet isolation process, such as organ transportation, enzyme perfusion, pancreas digestion, islet purification, tissue recombination, and islet bagging, in 12 TPIAT cases. The quantified miRNA information was then correlated with the corresponding TPIAT recipient's posttransplantation endocrine graft function parameters-C-peptide level, SUITO index, glycated hemoglobin, and exogenous insulin requirement-for validation of the biomarkers as a way to monitor islet damage during clinical islet isolations.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, found a detrimental effect of fibrosis and acinar atrophy in the pancreas on islet yield . Preliminary reports suggested that islet oxygen consumption rate (OCR) , islet size index , and finally miR‐375 and miR‐200c could have some predictive values as well.…”
Section: Discussionmentioning
confidence: 97%
“…Following up a total pancreatectomy with islet autotransplantation (TPIAT) patients for 1-year post-transplantation ( n = 31) revealed that miR-200c correlates with the islet metabolic transplantation outcomes. The data showed that high relative miR-200c expression (< 1.5) was associated with a favourable engraftment function and with less insulin dependence [ 66 ]. These early observations need to be followed up with large longitudinal studies.…”
Section: Microrna In Assessing the Outcomes Of Clinical Islet Transplmentioning
confidence: 99%
“… miR-200c could be a novel biomarker for predicting metabolic graft function post the TPIAT procedure. [ 66 ] Unmethylated INS DNA a CpG -206 & CpG-135 Plasma and whole Blood samples 41–53 Day 1 and day 14 Nested methylation-specific PCR Whole blood samples: The level of unmethylated INS rose significantly 1-day post the graft; the signal remained elevated 14 days post the graft. Plasma samples: The level of unmethylated INS was significantly elevated 1-day post the graft, and fell by the 14th day after the graft.…”
Section: Dna Methylation In Assessing the Outcomes Of Clinical Islet mentioning
confidence: 99%